Aspects Impacting Financial Statements’ Integrity - Putri, Anike; Aulia, Azwani; Jisika (Indonesian Scientific Publication, 2024)
The purpose of this study is to investigate how the integrity of financial statements in banking sector companies listed on the Indonesian Stock Exchange for the years 2021–2023 is affected by financial distress, auditor independence, and board gender diversity. The quantitative descriptive approach was the research methodology employed in this study. The population in this study are banking sector companies listed on the Indonesia Stock Exchange in 2021-2023, totaling 43 companies. Based on the sampling technique with purposive sampling, a sample of 10 companies was obtained. The company's annual report served as the source of the secondary data used. Panel data regression analysis is the data analysis model that is employed. The integrity of financial statements in banking sector companies listed on the Indonesian Stock Exchange for the year 2021-2023 is partially and simultaneously impacted by financial distress, auditor independence, and board gender diversity, according to the results of statistical studies.